MENGUAK REALITAS PRAKTIK SEDEKAH BUMI DI DESA CIASMARA KECAMATAN PAMIJAHAN KABUPATEN BOGOR - R. Atang Supriatna; Yogaprasta Adi Nugraha (UNIVERSITAS PAKUAN, 2020)
Agriculture is one of the important sectors that contribute to Indonesian national income. However, agricultural development currently has a tendency to increase productivity it impacts on the agricultural system which tends to make agriculture as